Persepsi Konsumen Akan Hygiene dan Sanitasi terhadap Keputusan Pembelian Makanan pada Pedagang Kaki Lima: Studi Kasus di Kawasan Wisata Alun-alun Sumedang - Luthfiyah Nur Cholis; Woro Priatini; Hurry Mega Insani (JURNAL GASTRONOMI INDONESIA, 2022)
Consumer perception is a condition that can be known, that someone is interested in buying something if it is influenced by the situation he faces. Hygiene and sanitation itself is the first element and an important requirement that must be considered in choosing food so that it is clean and safe. Healthy, safe and quality food is one of the important factors in improving one's health status because the purpose of eating is not just to be full, but needs to be nutritious and can meet the body's needs. Therefore, this study discusses consumer perceptions of hygiene and sanitation on purchasing decisions for food sold by street vendors in the Sumedang Square Tourism Area. This starts from the food processing process, the process of serving food and food storage used by street vendors. The method used in this research is descriptive quantitative with the help of SPSS application to calculate the answers that have been obtained. As a result, significantly (Pvalue < 0.05) street vendor consumers in the Sumedang Square Tourism Area were able to apply their knowledge of hygiene and sanitation in buying food from street vendors.